2022
DOI: 10.1148/radiol.212137
|View full text |Cite
|
Sign up to set email alerts
|

MRI Radiogenomics of Pediatric Medulloblastoma: A Multicenter Study

Abstract: Background: Radiogenomics of pediatric medulloblastoma (MB) offers an opportunity for MB risk stratification, which may aid therapeutic decision making, family counseling, and selection of patient groups suitable for targeted genetic analysis.Purpose: To develop machine learning strategies that identify the four clinically significant MB molecular subgroups. Materials and Methods:In this retrospective study, consecutive pediatric patients with newly diagnosed MB at MRI at 12 international pediatric sites betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…Non-invasive methods have made great advances with the identification of molecular subtypes based on DNA methylation. Similarly, as another clinical evaluation method, magnetic resonance imaging (MRI) also helps the differentiation of medulloblastoma from other pediatric brain tumors and risk stratification based on different features of T1 and T2-weighted MRI ( Duc et al, 2020 ; Minh Thong and Minh Duc, 2020 ; Zhang et al, 2022 ). In addition, cellular proliferation plays an essential role in tumor content, especially in highly malignant cancers ( Gu et al, 2021 ; McCarthy et al, 2021 ; Newman et al, 2021 ; Qiu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive methods have made great advances with the identification of molecular subtypes based on DNA methylation. Similarly, as another clinical evaluation method, magnetic resonance imaging (MRI) also helps the differentiation of medulloblastoma from other pediatric brain tumors and risk stratification based on different features of T1 and T2-weighted MRI ( Duc et al, 2020 ; Minh Thong and Minh Duc, 2020 ; Zhang et al, 2022 ). In addition, cellular proliferation plays an essential role in tumor content, especially in highly malignant cancers ( Gu et al, 2021 ; McCarthy et al, 2021 ; Newman et al, 2021 ; Qiu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the application of the proposed radiogenomics approaches in real clinical practice is still hampered by the several concerns, therefore limiting the role of the radiogenomics to research purposes by mostly reconstructing predictive models with a potential use to develop individualized treatments to ultimately affect patients’ prognosis [ 81 , 82 ]. In BC, the radiological imaging and the plethora of “omics” science would represent a significant improvement for patients if combined with genomic data, which have been already strictly correlated with the prognosis [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 17 optimal radiomics features were selected, containing 13 texture features and 4 intensity features. A multicenter study of 263 patients from 12 children’s hospitals reported that texture features and first-order intensity features contributed the most to improving the predictive efficacy of the model ( Zhang et al, 2022 ). In the study by Yan et al (2020) , three texture features and eight intensity features were extracted to construct the model.…”
Section: Discussionmentioning
confidence: 99%